(untitled) (Damascus University Journal of agriculture sciences, 2026)
This research was carried out in the field in Daraa Governorate during one agricultural season in 2022, with the aim of studying the effect of different rates of tomato waste compost and mineral fertilizer on the availability of macronutrient elements (NPK) and potato productivity in clay soil. A randomized complete block design (R.C.B.D.) was used with six treatments and three replications. The treatments were as follows: (T0): Control without any addition, (T1): 100% mineral fertilizer, (T2): 75% mineral fertilizer and 25% compost of tomato plant waste. (T3): 50% mineral fertilizer and 50% compost of tomato plant waste, (T4): 25% mineral fertilizer and 75% compost of tomato plant waste, (T5): 100% compost of tomato plant waste; mineral and organic nitrogen fertilizers was added according to the plant’s need for nitrogen. The results showed the effective role of tomato plant waste compost in increasing the soil’s total nitrogen content, as the two treatments (T5) and (T4) outperformed the control treatment, and the percentage increase in the soil’s total nitrogen content was (44.83% and 41.38%), respectively. The soil content of available phosphorus and potassium also increased in direct proportion to the increase in the rates added from tomato plant waste compost. The percentage increase in the soil content of available phosphorus and potassium in the treatment (T5) compared to the control treatment was (106.80% and 21.41%), respectively; which was reflected positively on the content of these two elements in the leaves. The results also showed that composting tomato plant waste contributed to increasing productivity and reducing the amount of mineral fertilizers by 25%.